High-level cryIVD and cytA gene expression in Bacillus thuringiensis does not require the 20-kilodalton protein, and the coexpressed gene products are synergistic in their toxicity to mosquitoes - Cheng Chang; Yong-Man Yu; Shu‐Mei Dai; S.K. Alex Law; Sarjeet S. Gill (1993)
Interactions among the 20-kDa protein gene and the cytA and cryIVD genes located in a 9.4-kb HindIII fragment were studied. A series of plasmids containing a combination of these different genes was constructed by using the Escherichia coli/Bacillus thuringiensis shuttle vector pHT3101. The plasmids were then used to transform an acrystalliferous strain, cryB, derived from B. thuringiensis subsp. kurstaki. The results from sodium dodecyl sulfate-polyacrylamide gel electrophoresis and immunoblot analyses suggest that although the 20-kDa protein is required for the efficient CytA protein production in E. coli, it is not required in B. thuringiensis. With or without the truncated 20-kDa protein gene, the CtyA and/or CryIVD proteins are produced and form parasporal inclusions in B. thuringiensis cells. However, more-efficient expression is obtained when a second protein, probably acting as a chaperonin, is present. In addition, the time course studies show that the CytA and CryIVD proteins are coordinately produced. Both the crude B. thuringiensis culture and purified inclusions from each recombinant B. thuringiensis strain are toxic to Culex quinquefasciatus larvae. The parasporal inclusions formed in B. thuringiensis cells are mosquitocidal, with CytA synergizing CryIVD toxicity.